Dividend Policy in Indonesian Companies: Does Corporate Governance Matter? - ., Zaitul; Ridwan, Muhammad; Pratiwi, Hanna (International Journal of Engineering and Technology, 2018)
This study investigates whether corporate governance matters with regards to the dividend policy in Indonesian companies. Previous studies on this subject have mostly been done in developed countries, which have adopted the common law, such as in the US and the UK.   This study uses 26 companies operating in the finance industry. Secondary data is used from several sources, such as the annual report and financial statement and related websites. This study uses an independent sample t-test to analyse the data. Corporate governance matters for dividend policy in Indonesian companies. It is evidenced by the fact that there is a significant difference in managerial ownership and board size between dividend paid and dividend not paid. Profitability also differs between dividend paid and dividend not paid companies; companies with higher profitability tend to pay dividend. This study provides empirical evidence that corporate governance matters for dividend policy in Indonesian companies. There are two contributions of this study: the result confirms the resource dependence theory and the convergence governance hypothesis.